Integration of Asean-5 Stock Markets: A Revisit - Bakri Abdul Karim; Zulkefly Abdul Karim (Asian Academy of Management Journal of Accounting and Finance, 2012)
This study re-examines the integration among five selected ASEAN emerging stock markets (Malaysia, Thailand, Indonesia, the Philippines and Singapore) based on Autoregressive Distributed Lag (ARDL) bound testing approach proposed by Pesaran, Shin and Smith (2001). This study finds that the stock markets in the ASEAN region are integrated during the pre-, post-1997 and post U.S. subprime financial crisis. In line with many studies on international interdependences of stock markets, our study finds that the ASEAN stock markets are moving towards more integration among themselves, especially following the global financial crisis. This implies that the long-run diversification benefits that can be earned by investors across the ASEAN markets tend to diminish. In addition, there is a need for policy coordination among ASEAN region to mitigate the impact of financial fluctuations, as the stock markets are interdependent.